What drives the H-abstraction reaction in bio-mimetic oxoiron-bTAML complexes? A computational investigation - Mukherjee, Anagh (Physical Chemistry and Chemical Physics, 2018)
Monomeric iron-oxo units have been confirmed as intermediates involved in the C–H bond activation in various metallo-enzymes. Biomimetic oxoiron complexes of the biuret modified tetra-amido macrocyclic ligand (bTAML) have been demonstrated to oxidize a wide variety of unactivated C–H bonds. In the current work, density functional theory (DFT) has been employed to investigate the hydrogen abstraction (HAT) reactivity differences across a series of bTAML complexes. The cause for the differences in the HAT energy barriers has been found to be the relative changes in the energy of the frontier molecular orbitals (FMOs) induced by electronic perturbation.